2022
DOI: 10.1139/cjfas-2021-0270
|View full text |Cite
|
Sign up to set email alerts
|

Fish length back-calculation from scales: advancing methodology and correction of bias

Abstract: Fish length back-calculation from hard structures (e.g., scales, otoliths, spines, etc.) is a commonly used method to reconstruct individual growth rates and sizes at age/stage in the absence of an intensive sampling–resampling timeseries. However, reliable estimates via these methods require the empirical validation of multiple assumptions about the growth of these hard structures. Here, we focus on reducing bias in scale-based back-calculations and validating proposed improvements using archived scales from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 62 publications
0
1
0
Order By: Relevance
“…Measurements were repeated if the sum of distances between points differed by more than 2.5% from the length of the transect. The Fraser–Lee method (Bailey et al 2022) was then used to estimate fork length at the time the antepenultimate circuli was formed and recent growth represents the difference between these two measurements. Previous studies have indicated that subyearling Chinook Salmon deposit scale circuli in proportion to somatic growth and that four circuli may be formed per month during the spring and summer (Walker and Sutton 2016).…”
Section: Methodsmentioning
confidence: 99%
“…Measurements were repeated if the sum of distances between points differed by more than 2.5% from the length of the transect. The Fraser–Lee method (Bailey et al 2022) was then used to estimate fork length at the time the antepenultimate circuli was formed and recent growth represents the difference between these two measurements. Previous studies have indicated that subyearling Chinook Salmon deposit scale circuli in proportion to somatic growth and that four circuli may be formed per month during the spring and summer (Walker and Sutton 2016).…”
Section: Methodsmentioning
confidence: 99%